Analisis Perbandingan Kesejahteraan Pekerja di Kota dan Kabupaten Mojokerto - Tirtana, Zevita Praja Tsalas (Jurnal Ilmu Ekonomi JIE, 2023)
The aims of this research are to compare and analyze differences in welfare in the city and Mojokerto regency. This study used a comparative quantitative method by distributing questionnaires to workers in the City and Regency of Mojokerto. The results of this questionnaire were tested using the normality test, homogeneity test and the Independent T-Test. From the results of the Independent T-Test it was found that the Sig. (2-tailed) 0.001 < 0.05 where there are differences in workers welfare between Mojokerto City and Regency. From the results of the questionnaires it is known that the minimum wage of workers, the level of education of workers, work facilities and health insurance affect the welfare of workers. From the research results it is also known that workers in Mojokerto City are more prosperous than those in Mojokerto Regency.   Tujuan dari penelitian ini untuk mengetahui perbandingan dan menganalisis perbedaan kesejahteraan di Kota dengan Kabupaten Mojokerto. Penelitian ini menggunakan metode kuantitatif komparatif dengan membagikan kuisiner ke pekerja di Kota dan Kabupaten Mojokerto. Hasil kuisioner ini diuji menggunakan uji normalitas, uji homogenitas dan uji Independent T-Test. Dari hasil pengujian Independent T-Test didapatkan bahwa nilai Sig. (2-tailed) 0.001 < 0.05 dimana terdapat perbedaan kesejahteraan pekerja antara Kota dan Kabupaten Mojokerto. Dari hasil kuisioner diketahui bahwa upah minimum pekerja, tingkat pendidikan pekerja, fasilitas kerja dan jaminan kesehatan mempengaruhi kesejahteraan pekerja. Dari hasil penelitian juga diketahui bahwa pekerja di Kota Mojokerto lebih sejahtera daripada di Kabupaten Mojokerto.